Birth preparedness and complication readiness among husbands and its association with skilled birth attendance in southern Ethiopia - Yordanos Gizachew Yeshitila; Peter Memah (BMC, 2022)
Abstract Introduction Birth preparedness and Complication Readiness (BPCR) promotes prompt use of skilled delivery and readiness for any complications to reduce delays in the provision of emergency care. Husband's involvement in preparation for childbirth is one way to mitigate life-threatening delays in providing care during childbirth. The current study assessed the association of the husband's involvement in birth preparedness and complication readiness with the use of skilled birth attendants. Method A community-based cross-sectional study was conducted among 1,432 husbands. Study participants were selected from Arbaminch university health and demographic surveillance sites. Data were collected electronically using the Open Data Kit. The data were exported to STATA version 16 for analysis. Descriptive statistics were computed to describe the sociodemographic and reproductive variables of the study. The associations between birth preparedness and complication readiness practice and birth in the presence of a skilled birth attendant were assessed using multiple logistic regressions after adjusting for known confounders. Explanatory variables on bivariate logistic regression analysis were entered into multivariable logistic regression analysis, and a p-value of less than 0.05 was used to ascertain statistical significance. Results Mean age of respondents was 33.7 (SD ± 6.2) years. Of all the respondents, 140 (10.3%) had made at least three preparations according to birth preparedness and complication readiness. After controlling for confounders through multivariable logistic regression, giving birth in the presence of a skilled birth attendant consistently increased with husbands involved in birth preparedness and complication readiness (AOR = 4.1, 95% CI: 2.5-6.9). Husbands whose wives had complications during previous pregnancy were 33% less likely to have skilled birth attendants (AOR = 0.67, 95% CI: 0.49-0.917). Moreover, husbands whose houses were near the health facilities were more likely to have skilled birth attendants for their wives (AOR = 3.93, 95% CI: 2.57-6.02). Conclusion Husband's involvement in birth preparedness and complication readiness is strongly associated with using skilled birth attendants in Ethiopia. It is imperative that when designing husband's involvement programs targeting birth preparedness and complication readiness, programs and strategies should focus on enhancing activities that are inclusive of husbands in birth preparedness and complication education.